2019
DOI: 10.4236/ojcm.2019.92008
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reliability-Enhanced Mechanical Characterization of Non-Crimp Fabrics: How to Compare Two Force-Displacement Curves against a Null Material Hypothesis

Abstract: Detailed characterization of fabric reinforcements is necessary to ensure the quality of manufactured composite parts, and subsequently to prevent structural failure during service. A lack of consensus and standardization exists in selecting test methods for the mechanical characterization of fabrics. Moreover, in reality, during any experimentation there are sources of uncertainties which may result in inconsistencies in the interpretation of data and the comparison of different testing methods. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Results indicated that while the stress distribution for the pure NBR is more skewed toward higher values, the CVaR of NGP-blended NBR is 80% higher. The two cumulative distribution curves were also compared via a two-way ANOVA similar to the method used in ref , confirming that the two distributions are statistically different ( p -value < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that while the stress distribution for the pure NBR is more skewed toward higher values, the CVaR of NGP-blended NBR is 80% higher. The two cumulative distribution curves were also compared via a two-way ANOVA similar to the method used in ref , confirming that the two distributions are statistically different ( p -value < 0.05).…”
Section: Resultsmentioning
confidence: 99%